2020
DOI: 10.3390/foods9121838
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Recombinant Single-Domain Antibody for Gluten Detection in Foods Using the Pichia pastoris Expression System

Abstract: The detection of gluten in foodstuffs has become a growing concern in food allergen management as a result of the high ratio of population sensitive to the main gluten-containing cereals. In this study, a promising single-domain antibody previously isolated by phage display (dAb8E) was produced in Pichia pastoris resulting in high levels of the antibody fragment expression (330 mg/L). The purified dAb8E was proved to specifically bind to gluten proteins from wheat, barley and rye, exhibiting no cross reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Besides, the ingestion of gluten-containing cereals would trigger gluten-related disorders. Garcia-Garcia A et al [32] developed a sandwich ELISA to detect gluten in food products. The yeast P. pastoris was employed to produce a recombinant single-domain antibody (dAb8E) by phage display technology, which acted as a novel biorecognition molecule to develop an immunoassay with a LOD of 0.12 ng mL -1 and a linear range of 0.1-10 µg mL -1 .…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Besides, the ingestion of gluten-containing cereals would trigger gluten-related disorders. Garcia-Garcia A et al [32] developed a sandwich ELISA to detect gluten in food products. The yeast P. pastoris was employed to produce a recombinant single-domain antibody (dAb8E) by phage display technology, which acted as a novel biorecognition molecule to develop an immunoassay with a LOD of 0.12 ng mL -1 and a linear range of 0.1-10 µg mL -1 .…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Currently, the most common methods for quantitative detection of wheat gluten, include the antibody-based immunoassay method [e.g., enzyme-linked immunosorbent assay (ELISA)] and DNA-based method [e.g., quantitative real-time polymerase chain reaction (qPCR)]. García-García et al reported a sandwiched ELISA for gluten detection with a limit of detection (LOD) of 0.12 µg/mL [15].…”
Section: Introductionmentioning
confidence: 99%
“…Novel single-domain (dAb) recombinant antibodies [23], suitable for the development of gluten detection ELISA systems, have been recently obtained from directed evolution processes based on phage display technology [24]. In this work, the use of Fabs is proposed instead of dAbs because of their enhanced stability and a bigger paratope [25].…”
Section: Introductionmentioning
confidence: 99%